Safdar Faisal
Proof of $$N=\sum^\infty_{a=1}\sum^\infty_{b=1}\sum^\infty_{c=1}\mathrm{\frac{ab(3a+c)}{4^{a+b+c}(a+b)(b+c)(c+a)}}=\frac{1}{2}\sum^\infty_{a=1}\sum^\infty_{b=1}\sum^\infty_{c=1}\frac{1}{4^{a+b+c}}$$
Sep 14, 2020 at 19:53, 18 minutes total – 14 messages, 2 users, 0 stars
Bookmarked Sep 14, 2020 at 20:11 by Safdar Faisal
A
Aug 18, 2020 at 13:18, 5 minutes total – 21 messages, 2 users, 0 stars
Bookmarked Aug 20, 2020 at 6:48 by Safdar Faisal
Phenyl Migration
Aug 14, 2020 at 15:04, 1 minute total – 5 messages, 1 user, 0 stars
Bookmarked Aug 16, 2020 at 7:25 by Safdar Faisal